TEXT DIMENSION OF GOVERNMENT’S ATTENDANCE POLEMIC AT CELEBRITY WEDDING: A CRITICAL DISCOURSE ANALYSIS - Lazuar Azmi Zulferdi; Rahma Cahyaningrum (IdeBahasa, 2023)
Polemic about the government’s attendance at celebrity weddings during COVID-19 caused various negative responses, particularly in online news. The present research aims at identifying the text dimension representing news about the government’s attendance polemic at a celebrity wedding in The Jakarta Post and Tempo.co English. The qualitative method is employed to analyze two articles entitled “The wedding that Sparked a Backlash” and “State Secretariat Blasted for Posting Jokowi’s Celebrity Wedding Attendance” using Fairclough’s Critical Discourse Analysis (2010) as the theoretical approach. Simak (observation) method is used to collect the data and padan (identity) method is used to analyze the data by Sudaryanto (2015). The results showed that The Jakarta Post is more neutral in representing the polemic of government presence since it contains views from four parties. Meanwhile, Tempo.co English tends to elicit a negative impression of the government as it includes information from a one-sided view. However, both online news represents similar political ideology since it highlights the political purpose of the government’s existence at celebrity weddings.